Penerapan Analisis SWOT pada Keboon Kopi Cafe & Resto - Vincent Vincent; Iwan Bipianto; Wasiman Wasiman (LPPM Universitas Putera Batam, 2023)
This study applies SWOT analysis to Keboon Coffee Cafe and Resto, a culinary business located in Batam City. Its purpose is to provide insights to the management of Keboon Coffee Cafe & Resto to effectively manage the business in the long term. The Strengths of this business include its strategic location, attractive and Instagram-worthy interior design, comprehensive facilities, spacious premises, a diverse menu offering both Western and Indonesian cuisine, high-quality food at affordable prices, active social media promotion, and a strong reputation among customers. The business also has some Weaknesses, such as challenges with parking during peak hours, relatively slow food service, limited menu availability during certain hours, inflexible beverage packages, the need for ongoing innovation in food and beverages, and the necessity of adjusting portion sizes and prices. Opportunities for Keboon Coffee Cafe & Resto include its central and strategic location in the city, the broad appeal of its food and beverage concept across different demographics, and its family-friendly atmosphere. However, there are also Threats to consider, such as competition from similar businesses in the vicinity, business reliance on a leased location, which could impact long-term sustainability, and the continual need for innovation in menu offerings. This study uses a qualitative descriptive approach with key informants as the primary source of data collection.